PHLDA1 modulates microglial response and NLRP3 inflammasome signaling following experimental subarachnoid hemorrhage - Lai, Jinqing; Chen, Genwang; Wu, Zhe; Yu, Shaoyang; Huang, Rongfu; Zeng, Yile; Lin, Weibin; Fan, Chunmei; Chen, Xiangrong (Frontiers in Immunology, 2023)
Balancing microglia M1/M2 polarization is an effective therapeutic strategy for neuroinflammation after subarachnoid hemorrhage (SAH). Pleckstrin homology-like domain family A member 1 (PHLDA1) has been demonstrated to play a crucial role in immune response. However, the function roles of PHLDA1 in neuroinflammation and microglia polarization after SAH remain unclear. In this study, SAH mouse models were assigned to treat with scramble or PHLDA1 small interfering RNAs (siRNAs). We observed that PHLDA1 was significantly increased and mainly distributed in microglia after SAH. Concomitant with PHLDA1 activation, nod-like receptor pyrin domain-containing protein 3 (NLRP3) inflammasome expression in microglia was also evidently enhanced after SAH. In addition, PHLDA1 siRNA treatment significantly reduced microglia-mediated neuroinflammation by inhibiting M1 microglia and promoting M2 microglia polarization. Meanwhile, PHLDA1 deficiency reduced neuronal apoptosis and improved neurological outcomes after SAH. Further investigation revealed that PHLDA1 blockade suppressed the NLRP3 inflammasome signaling after SAH. In contrast, NLRP3 inflammasome activator nigericin abated the beneficial effects of PHLDA1 deficiency against SAH by promoting microglial polarization to M1 phenotype. In all, we proposed that PHLDA1 blockade might ameliorate SAH-induced brain injury by balancing microglia M1/M2 polarization via suppression of NLRP3 inflammasome signaling. Targeting PHLDA1 might be a feasible strategy for treating SAH.